Influence of temperature on breaking dormancy and germination of Brachiaria (Research, Society and Development, 2020)
The Seed Analysis Rules (SAR) recommend scarification with sulfuric acid and moistening of the substrate with 0.2% potassium nitrate to break the dormancy of Brachiaria and its germination. This work aimed to evaluate the use of an alternative methodology to the treatments recommended by RAS by cooling the seeds to 4 ° C and immersion in distilled water at room temperature and 0.2% sodium nitrate for two hours, to break down dormancy and germination of B. decumbens Stapf cv. Basilisk and B. brizantha (Hochst. Ex. A. Rich.) Stapf cv. Marandu and cv. Piatã. For this purpose, a 3 × 2 × 2 Fully Randomized Design was structured in gerbox to compare the germination percentages of seeds kept at room temperature and soaked in H2O and H2O + NaNO3 with chilled seeds and soaked in H2O and H2O + NaNO3. DIC was also structured in a roll, in addition to the PG (%), to evaluate the length of the aerial part (cm) and root (cm) and total fresh weight (g). Tetrazolium tests and germination speed index were also performed. The results were submitted to the Tukey test (p≤0.05). The germination percentage evaluated at 14 days was affected by cultivars and temperature, with the seeds refrigerated at 4ºC surpassing those kept at room temperature (an increase of 220%). There was no significant difference for the imbibition factor in H2O or H2O + NaNO3.